Entrepreneurship, Corporate Social Responsibilities, and Innovation Impact on Banks’ Financial Performance - Wei, Jianhua; Xiong, Rong; Hassan, Marria; Shoukry, Alaa Mohamd; Aldeek, Fares Fawzi; Khader, J. A. (Frontiers in Psychology, 2021)
The basic aim of this research is to calculate the influence of innovation, corporate social responsibilities (CSR) and entrepreneurship on the monetary performance of banks in five different countries included Qatar, Pakistan, China, US and France. Further research measuring several factors related to the innovation process in entrepreneur filed. The secondary data are collected to measure relationship and innovative workforce activities and their effect on financial performance. The data collected from the website of 25 banks of different countries included Islamic and conventional banks. This paper uses different econometric analysis such as descriptive statistical analysis for the description of data, correlation coefficient test for measuring the inter-correlation, used ordinary least square regression analysis to determine the impact of dependent and independents variables. In this research paper, entrepreneurship, CSR and innovation are independent variables that included board size, frequency of assemblies, and self-employed with large shareholders as sub-parts of entrepreneurship. On the other hand, the financial performance as dependent variable returns on assets ROA, and return on equity ROE is a part of economic performance. The overall consequences in this study show that there is a significant relationship between them. The research analysis provided useful insights into the long-debated question regarding the relevance of entrepreneurship and CSR.